2021
DOI: 10.3390/joitmc7010011
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intention: Creativity, Entrepreneurship, and University Support

Abstract: To study the impact of perceived creativity disposition on entrepreneurial attitude and intentions, based on the theory of planned behavior, a model of the relationship between perceived creativity disposition and entrepreneurial intentions and attitude was constructed, relevant hypotheses were proposed, and the moderation mechanism of perception of university support on perceived creativity disposition and entrepreneurial intentions was also developed and analyzed. The study population included university bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 53 publications
11
88
0
2
Order By: Relevance
“…Regarding H4, we found that creativity had a positive and significant effect on entrepreneurial intention. This finding is in line with several previous studies (Hu et al, 2018;Anjum et al, 2021), which remarked that individuals with a high level of creative minds are more likely to peruse a career in entrepreneurship. Creativity is all about something new and innovative and individuals who have creative minds are more capable to articulate innovative ideas into a reality that ultimately leads toward the entrepreneurial intention.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding H4, we found that creativity had a positive and significant effect on entrepreneurial intention. This finding is in line with several previous studies (Hu et al, 2018;Anjum et al, 2021), which remarked that individuals with a high level of creative minds are more likely to peruse a career in entrepreneurship. Creativity is all about something new and innovative and individuals who have creative minds are more capable to articulate innovative ideas into a reality that ultimately leads toward the entrepreneurial intention.…”
Section: Discussionsupporting
confidence: 93%
“…It allows individual to have an opportunity in entrepreneurship tasks such as identifying an opportunity, making business feasibility, and implementing a business plan. In line with the entrepreneurship research in the context of developed nations, the role of entrepreneurial education, entrepreneurial mindset, and creativity in entrepreneurship have been discussed by several researchers (Shi et al, 2020;Anjum et al, 2021). Some studies have outlined that individuals with a high level of entrepreneurial education, entrepreneurial mindset, and creativity are more prone to start their businesses (Hu and Ye, 2017;Handayati et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Second, this technique is generally suitable when complex models are examined [85], particularly involving mediation [86]. Third, being a solid component-based approach, many prior marketing [87], management [88][89][90][91][92], and entrepreneurship [93][94][95][96][97] studies have employed this approach. PLS-SEM involves two stages.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire is distributed by e-mail via the Internet in the form of electronic copy and the hard copy is distributed by personal mail and post. SEM-PLS route modelling was used to evaluate the proposed theoretical framework in this study (Anjum, Amoozegar, Nazar, & Kanwal, 2020;Anjum, Farrukh, Heidler, & Tautiva, 2021;Anjum, Sharifi, Nazar, & Farrukh, 2018). The social exchange theory was chosen for this study because it has been used to address employee engagement by describing the factors that lead to employee engagement or disengagement.…”
Section: Methodsmentioning
confidence: 99%